Characterization, distribution, sources and origins of aliphatic hydrocarbons from surface sediment of Prai Strait, Penang, Malaysia: a wide spread anthropogenic input - Sakari, Mahyar (Thai Society of Higher Education, 2008)
Persistent organic pollutants such as petroleum hydrocarbons are one of the most serious and important class of pollutants that face to many countries including Malaysia. Aliphatic hydrocarbons contain straight chain alkane; derive from anthropogenic and natural sources to the marine environment. The multi-purpose strait of Prai is located in the Northwest of Peninsular Malaysia plays an important economic role in the Southeast Asia. Twenty surface sediment samples were collected using Eckman dredge to measure the concentration and determine the characterization, sources and origins of the aliphatic hydrocarbons in December 2006. Samples (top 4 cm) were extracted with Soxhlet, treated with activated copper and subjected to 2 steps column chromatography for purification and fractionation. Alkane fraction injected into Gas Chromatography–Flame Ionization Detector (GC-FID) for instrumental analysis. The results showed that total n-alkane concentrations are ranging from 512 to 10770 ng/mg d. w. Carbon Preferences Index (CPI) revealed an extreme widespread anthropogenic input and naturally derived (CPI= 0 to 4.88) hydrocarbons in the study area. The ratio of C31/C19 indicated that natural hydrocarbons are generating from terrestrial vascular plants and transferring by rivers. The characteristics of Major Hydrocarbons provided evidences that oil and its derivatives either fresh or degraded are the major contributors of the pollution in the study area. Statistical approaches also confirmed that 85% of study area affected by oil sources of pollution. It is seen that aliphatic hydrocarbons mostly transfer by lateral input to the marine environment than atmospheric movements.